The influence of match outcome on running performance in elite Gaelic football. Issue 3 (2nd September 2017) - Mangan, Shane; Malone, Shane; Ryan, Martin; McGahan, Jason; O'neill, Cian; Burns, Con; Warne, Joe; Martin, Denise; Collins, Kieran
ABSTRACT: Introduction: Match outcome has been linked to running performance in many sports; however, the association has not yet been examined in Gaelic football.Methods: GPS technologies (4-Hz, VX Sport, Lower Hutt, New Zealand) were used with 5 elite Gaelic football teams over a period of 5 years (2012–2016), amounting to 95 matches. In total, 780 full match data sets were collected. Game movements were divided into total distance and high-speed distance (≥17 km h −1 ). Match outcomes were divided into big losses (≥6 points), small losses (≤5points), draws, small wins (≤5 points) and big wins (≥6 points).Results: Team ( P ≤ 0.001), playing position ( P ≤ 0.001) and match outcome ( P ≤ 0.034) had a significant effect on total and high-speed distance. In the first ( P = 0.008) and second ( P = 0.002) quarters of games players ran significantly less high-speed distance in big losses in comparison to draws. In the fourth quarter, players ran significantly less high-speed distance in big losses than in draws ( P = 0.001), small wins ( P = 0.044) and big wins ( P = 0.011).Conclusion: The current study confirms that running performance is a contributing factor to match outcome in Gaelic football. Coaches should be aware how contextual factors can influence running performance.